Family Involvement in Mental Health Recovery: Systemic Barriers and Supportive Strategies for Enhancing Treatment Adherence and Outcomes - Handayani, Annisa Awalia (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2022)
Taxation policies, digital economy expansion, and sustainability initiatives are key determinants of global economic growth. This study investigates their combined impact through a qualitative case study in Indonesia. The research employs in-depth interviews with academics, economists, policymakers, and business leaders to explore how these factors shape economic development. Findings reveal that taxation policies significantly influence investment and consumption, with excessive tax burdens potentially stifling economic growth. The rise of the digital economy has reshaped labor markets, leading to both employment displacement and new job opportunities requiring digital competencies. Sustainability policies, while essential for long-term economic stability, necessitate inclusive strategies to avoid disproportionately affecting vulnerable populations. The study contributes to the existing body of knowledge by highlighting the interconnectedness of fiscal, digital, and sustainability policies in driving economic growth. It emphasizes the need for policymakers to design balanced tax structures, invest in digital skills development, and implement sustainability policies that promote equitable economic progress. Future research should assess long-term trends in taxation, digital transformation, and sustainability on macroeconomic stability and social equity.